The Characteristics of Striped Catfish Oil (Pangasius hypophthalmus) Extracted by Dry Rendering Method at Different Temperatures - Dhita Ulfi Lestari; Sumardianto Sumardianto; Lukita Purnamayati (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Striped catfish (Pangasius hypophthalmus) is a high-fat fish compared to other freshwater fish like snakehead fish and carp. Striped catfish oil contains unsaturated and polyunsaturated fatty acids that are beneficial for health. The quality of catfish oil is affected by the extraction method, especially the preliminary heating temperature for the extraction. This study aimed to determine the effect of different heating temperatures on the characteristics of catfish oil and find the best heating temperature in the dry rendering process. This study used a completely randomized design with three different heating temperatures (80°C, 100°C and 120°C). The result showed that the extraction at various temperatures was significantly different on the yield, moisture content, peroxide value, iodine value, free fatty acids value and slip melting point, but not significantly different in sensory properties. A higher heating temperature could increase the yield percentage, free fatty acids values, peroxide values, iodine values, except to the moisture contents, slip melting point and fatty acid profiles. The best temperature was 100°C for 20 minutes with 9.09% yield, 1.44% moisture content, 1.72% free fatty acid, 15.82% iodine value and sensory of 7.65<µ<8.15. Based on the results, it can be concluded that the dry rendering temperature affects the characteristics of the catfish oil.